2003
DOI: 10.1016/s0006-3495(03)74621-9
|View full text |Cite
|
Sign up to set email alerts
|

FTIR Spectroscopy Demonstrates Biochemical Differences in Mammalian Cell Cultures at Different Growth Stages

Abstract: We have observed differences in the infrared spectra of viable fibroblast cells depending on whether the cells were in the exponential (proliferating) or plateau (nonproliferating) phase of growth. The spectral changes were observed even after correcting for cell number and volume, ruling out these trivial explanations. Several of the changes occurred for both transformed and normal cell lines and were greater for the normal cell line. The biochemical basis of the spectral changes was estimated by fitting the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(123 citation statements)
references
References 26 publications
9
113
1
Order By: Relevance
“…This difficulty may be lessened through careful choice of spectral intervals for integration, as was the approach adopted here. The spectral changes observed here are consistent with those previously observed in experiments utilising spectral decomposition [8], and as such support the approach adopted here. All measurements are normalised to the corresponding control measurement.…”
Section: Spectroscopic Assayssupporting
confidence: 90%
See 2 more Smart Citations
“…This difficulty may be lessened through careful choice of spectral intervals for integration, as was the approach adopted here. The spectral changes observed here are consistent with those previously observed in experiments utilising spectral decomposition [8], and as such support the approach adopted here. All measurements are normalised to the corresponding control measurement.…”
Section: Spectroscopic Assayssupporting
confidence: 90%
“…within the spectrum [8]. This difficulty may be lessened through careful choice of spectral intervals for integration, as was the approach adopted here.…”
Section: Spectroscopic Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet most of these differences were located in the DNA/RNA spectral region. Several studies have previously reported spectral differences for cells at different stages of the eukaryotic cell division cycle [1,2,13]. These differences are caused by the morphological and biochemical changes occurring within the cell division cycle.…”
Section: Resultsmentioning
confidence: 99%
“…Otherwise, the nucleic acid contribution of the spectrum is mostly due to cytoplasmic RNA, DNA being too tightly packed in the nucleus to allow the infrared radiation to cross through [1]. Meanwhile, Mourant et al demonstrated that the ratio RNA/lipid could be used to determine the proliferative status of mammalian cells [13]. A diagnostic advantage of the FT-IR spectroscopy in cancer research is that the development of a cancer DNA phenotype can be observed prior to the tumor formation, notably for prostate carcinomas [11].…”
Section: Resultsmentioning
confidence: 99%